Said Halim Paşa’da ahlak ve siyaset - Bulanık, Abdulhalit (My University, 2004)
Ahlak ve siyaset, düşünce tarihinin önemli iki konusu olarak günümüze kadar devam edegelmiştir. Bu iki kavram, bazen birbiriyle ilişkilendirilmiş bazen de müstakil olarak ele alınmıştır. İslam dininin ahlaka vurgu yapması ve Kur'an'da ahlaki kavramların yoğunlukta olması ve Kur'an'ın ahlaklı bireyler ve toplumlar oluşturma iddiası / telkini, ahlak-siyaset ilişkisinin Müslüman düşünürlerce sürekli incelenmesine sebep olmuştur. Modern dönemin düşünce yapısını iyi anlayabilmenin yolu, yakın tarihi iyi incelemek ve anlamaktan geçer. Osmanlı'nın son döneminde ortaya çıkan fikir hareketleri, farklı şekillerde etkilerini günümüze kadar sürdüregelmişlerdir. Yakın tarihimizin önemli fikir ve devlet adamı olan Said Halim Paşa, hem siyasi tecrübesiyle hem de savunduğu fikirlerle ahlak ve siyaset alanında eserler vermiştir. Hacmi küçük fakat anlamı büyük bu eserlerinde Said Halim Paşa, Doğu ve Batı toplumlarını karşılaştırmış, ahlak ile siyaset arasında ilişki kurarak, Batı'nın ahlak anlayışından doğan siyaset anlayışının ve kurumlarının bizim toplumumuza olduğu gibi uyarlanamayacağını savunmuştur. Son yıllarda Said Halim Paşa'nın görüşlerini ele alan çalışmaların aksine bu çalışmamızda biz, Paşa'nın ahlak ve siyaset görüşlerini ele aldık ve ağırlıklı olarak ahlak görüşleri ile siyaset görüşleri arasındaki ilişkiyi, dönemin de düşünce yapısını göz önünde bulundurarak ortaya koymaya çalıştık. Ethic and Politics are two important topics in the history of intellectual thought which is carried on till to our days. These concepts sometimes discussed together and sometimes independently. Because of the Islamic emphasize on ethic/ morals and because of the Quran's stress on ethics widely from a side; and from another side, the inspiration of Quran in order to establish morally uprighted persons and communities the Muslim intellectuals discussed the ethic-politic link/ relation continually. There is no doubt that the way of understanding the form/ structure of contemporary thought affiliated with studying and understanding the near history in a proper way. The intellectual movements which are arised in the late Otoman period has carried on its influences in different forms till to our time. An intellectual and important statesman of our near history Said Halim Pasa has given very significant works with his political experience and also with his thoughts which he has defended. In his -volumetrically small but by meaning comprehensive and significant- works Said Halim Pasa has compared the Eastern and Western communities and discussed the ethic(al) and politic(value)s with each other and has pointed out that the political understandings of west and its institutions which are a born/ result of its ethical understanding can not be transferred and adapted to our (Eastern) communities as they are. On the contrary to the works being prepared about Said Halim Pasa's thoughts; we have mainly taken into account Said Halim Pasa's ethical and political thoughts and we have largely emphasized on the the link/ relation between the ethical and political thoughts of Pasa and tried to explain them by taking into consideration the structure of intellectual thought of that period which is in question.
Keywords: İslam Felsefesi